2021
DOI: 10.3389/fneur.2021.744909
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes of Intravenous Thrombolysis in Mild Ischemic Stroke Patients

Abstract: Objective: This study assessed the characteristics of intravenous thrombolysis (IVT) with respect to early neurological deterioration (END) and functional outcome in mild ischemic stroke patients.Methods: Data were obtained from acute mild ischemic stroke patients (defined as having a National Institute of Health Stroke Score (NIHSS) ≤ 5) treated with IVT in our hospital from July 2017 to December 2020. END was defined as the NIHSS increased ≥1 over the baseline at 24 h after IVT. A modified Rankin scale (mRS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 31 publications
4
14
0
Order By: Relevance
“…In their study, the authors included several novel blood markers such as: Hhcy, HDL-C/LDL-C, which indicates that these lipid markers might be very important in the pathology of stroke ( Lv et al, 2020 ). Similar results were obtained from Huan Tang et al, and the 3-month poor outcome is related to the baseline elevated SBP, baseline NIHSS, prior hyperlipemia, cardioembolic stroke ( Tang et al, 2021 ). Few studies correlated the neurological outcome with logistic regression model rather than the nomogram ( Çetiner et al, 2018 ; Tork et al, 2020 ; Cui et al, 2022 ), and most of them were focusing on the complications in stroke patients after thrombolysis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In their study, the authors included several novel blood markers such as: Hhcy, HDL-C/LDL-C, which indicates that these lipid markers might be very important in the pathology of stroke ( Lv et al, 2020 ). Similar results were obtained from Huan Tang et al, and the 3-month poor outcome is related to the baseline elevated SBP, baseline NIHSS, prior hyperlipemia, cardioembolic stroke ( Tang et al, 2021 ). Few studies correlated the neurological outcome with logistic regression model rather than the nomogram ( Çetiner et al, 2018 ; Tork et al, 2020 ; Cui et al, 2022 ), and most of them were focusing on the complications in stroke patients after thrombolysis.…”
Section: Discussionsupporting
confidence: 82%
“…prior hyperlipemia, cardioembolic stroke (Tang et al, 2021). Few studies correlated the neurological outcome with logistic regression model rather than the nomogram (Çetiner et al, 2018;Tork et al, 2020;Cui et al, 2022) (Zhou et al, 2020).…”
Section: Confusion Matrix True Prediction False Predictionmentioning
confidence: 99%
“…Computed tomography, magnetic resonance and digital subtraction angiography, electrocardiography, and carotid ultrasound were used to determine the stroke etiology. The clinical outcome at 90 days after AIS was assessed using the mRS. An mRS ≥ 2 or death was defined as a poor prognosis [ 8 , 9 ]. The data were obtained using a telephone follow-up interview by a physician who was unaware of the patients’ clinical information and factor levels.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, identification of risk factors linked to poor outcomes in patients with mild AIS after IVT is crucial. Age, diabetes, the baseline NHISS, and large vessel occlusion are some of the factors that have been mentioned in prior investigations (3,8,9). Moreover, it has been proposed that serum biomarkers may play an important role in the prognosis of mild AIS in recent years.…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies reported that more than half of AIS patients present with mild stroke ( 1 , 2 ). Currently, there is no formal definition for mild AIS, but the majority of studies describe it as a National Institutes of Health stroke scale (NHISS) score ≤5 at admission ( 3 , 4 ). In the clinical guidelines published in December 2019, intravenous thrombolysis (IVT) was recommended for mild AIS patients with disabling symptoms ( 5 ).…”
Section: Introductionmentioning
confidence: 99%